Cunninghamella binariae, Mucor ardhlaengiktus, Mucor gigasporus and Umbelopsis changbaiensis, newly recorded species from amphibian feces and soil in Korea - Nguyen, Thuong T.t.; Hyde, Kevin D.; Lee, Hyang Burm (Phytotaxa, 2019)
Four strains, CNUFC SKT18002, CNUFC FKT18033, CNUFC SKT19001, and CNUFC SKT18228 were isolated during an investigation of fungi belonging to the orders Mucorales and Umbelopsidales from amphibian feces and soil samples in Korea. Based on morphological characteristics and the sequence analysis of the internal transcribed spacer (ITS) region and 28S rDNA sequences, the strains CNUFC SKT18002, CNUFC FKT18033, CNUFC SKT19001, and CNUFC SKT18228 were identified as Cunninghamella binariae, Mucor ardhlaengiktus, Mucor gigasporus, and Umbelopsis changbaiensis, respectively. To the best of our knowledge, the species C. binariae, M. ardhlaengiktus, M. gigasporus, and U. changbaiensis have not been previously reported in Korea.